2017
DOI: 10.1080/10410236.2017.1399509
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Risk Information in Direct-to-Consumer Prescription Drug Television Ads: A Content Analysis

Abstract: Direct-to-consumer (DTC) television ads for prescription drugs are required to disclose the product's major risks in the audio or audio and visual parts of the presentation (sometimes referred to as the "major statement"). The objective of this content analysis was to determine how the major statement of risks is presented in DTC television ads, including what risk information is presented, how easy or difficult it is to understand the risk information, and the audio and visual characteristics of the major sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In particular, DTCA has come under criticism for violating the FDA fair balance guideline by using distraction during the major statement. Researchers have found that pharmaceutical companies frequently present incongruent, positive visual imagery during auditory disclosures of negative risk information (Avery, Eisenberg, and Simon 2012; Kaphingst et al 2004; Macias, Pashupati, and Lewis 2007) or pair incongruent visual images with moderately fast-paced music and faster narration (Sullivan, Aikin, and Poehlman 2019).…”
Section: Research On Distraction In Dtcamentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, DTCA has come under criticism for violating the FDA fair balance guideline by using distraction during the major statement. Researchers have found that pharmaceutical companies frequently present incongruent, positive visual imagery during auditory disclosures of negative risk information (Avery, Eisenberg, and Simon 2012; Kaphingst et al 2004; Macias, Pashupati, and Lewis 2007) or pair incongruent visual images with moderately fast-paced music and faster narration (Sullivan, Aikin, and Poehlman 2019).…”
Section: Research On Distraction In Dtcamentioning
confidence: 99%
“…One concerning practice that frequently occurs during the major statement is the appearance of positively valenced imagery that is incongruent with the concurrent audio content discussing a drug’s risks (cf. Glinert 2005; Kaphingst et al 2004; Sullivan, Aikin, and Poehlman 2019; Sumpradit, Ascione, and Bagozzi 2004). Although FDA guidelines suggest that pharmaceutical advertisers should avoid presenting incongruous or distracting imagery during the auditory presentation of risk, little empirical research has considered whether such advertisers do in fact adhere to this standard.…”
mentioning
confidence: 99%
“…8,9 There is a wide literature on how to present quantitative information to facilitate understanding. 1014 Although content analyses have shown that few DTC television ads contain quantitative information about drug benefits and risks, 1517 providing quantitative information in DTC advertising has been recommended, 18 and previous studies have shown it can help consumers better understand benefit and risk information in print ads 1922 and television ads. 19…”
mentioning
confidence: 99%
“…For several products, this involves a substantial recitation of medical or technical terms. A recent content analysis (Sullivan, Aikin, & Poehlman, 2017) showed 96% of ads contained at least one medical term in the major statement, with an average of three terms per ad.…”
mentioning
confidence: 99%
“…Second, DTC television ads vary in voiceover speed, which often increases when the major statement is read (Sullivan et al, 2017). Among adults over 60 with hearing loss, Jenstad and Souza (2007) found participants' speech recognition scores were lower in conditions of rapid speech versus normal speech.…”
mentioning
confidence: 99%